SPEAKING ABOUT WASTING TIME - Maxmudxo’jayeva Ziyodaxon Isomitdinovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Introduction Time is one of the most valuable resources in human life. Unlike money or material possessions, time cannot be earned back once it is lost. Every person has the same twenty-four hours in a day, but people use this time differently. Some individuals spend their time productively, while others waste it on unimportant activities. Wasting time has become a common problem in modern society due to the influence of technology, social media, and poor planning. Understanding the causes and consequences of wasting time can help people manage their lives more effectively. What Does Wasting Time Mean? Wasting time means spending time on activities that do not bring meaningful results or help achieve personal goals. It does not mean that every minute must be spent working. Rest, hobbies, and entertainment are important parts of life. However, time becomes wasted when people spend excessive amounts of it on activities that provide little value. For example, many people spend hours scrolling through social media without learning anything useful. Others procrastinate by watching videos, playing games, or chatting online when they should be studying or working. These habits may seem harmless at first, but over time they can lead to serious problems.